(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The purpose of this study is to monitor the present status of water supply and sanitation facilities of primary school in Gaibandha Sadar, Bangladesh. Forty nine (49) primary schools were selected for this purpose. The study revealed that, about 86% school had shallow tube well as a source for their drinking water supply and sanitation. About 18% schools had no sanitation facility or inactive sanitation unit. Separate toilet facility for girls and teachers was found in about 69 and 55% schools respectively but only one school has separate toilet facility for male and female teacher. Availability of water, soap and hand washing facility inside girls and boys latrine is in average amount but in teachers toilet it was satisfactory. Most of the schools (69%) have active drainage system at water point where 41% schools have basket in all classes for dumping of solid wastes. In this regard, the proper management and monitoring of existing facilities are required to improve the present water supply and sanitation situation in primary schools of Bangladesh. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22050 J. Environ. Sci. & Natural Resources, 6(1): 113-116 2013